Polyvinylphenol (PVP) microcapacitors printed by laser-induced forward transfer (LIFT): multilayered pixel design and thermal analysis investigations. (11th March 2016) - Constantinescu, C; Rapp, L; Rotaru, P; Delaporte, P; Alloncle, A P
Abstract: Highlights Laser-induced transfer is used for the printing of multilayered microcapacitors The dielectric film is made of PVP, and the electrodes are made of Ag Thermal behaviour of the polymer is discussed with respect to the laser processing The structure and electrical properties of the capacitors are discussed Ag/polyvinylphenol (PVP) multilayered pixels are printed by laser-induced forward transfer (LIFT) technique for thin film microcapacitor applications. The third harmonic (3 ω /355 nm, τ   =  50 ps) of a solid state neodymium-doped yttrium aluminium garnet (Nd:YAG) laser source is employed throughout our LIFT experiments. By selecting adequate printing parameters (e.g. donor thickness, laser fluence, background pressure), we show how functional microcapacitors are fabricated. At ~350 μ m in lateral size and 300 nm thickness of the dielectric film, the pixels have capacities in the picofarad range. We discuss the laser influence during the pixel transfer process and highlight the polymer's thermal behaviour.